Overprinting porphyry‐type veinlets on the intrusive rocks and phreatomagmatic breccias in the Southwest prospect, southwestern Sto. Tomas II (Philex), Baguio District, Philippines. Issue 1 (13th October 2020) - Cirineo, Avriel Venis L.; Imai, Akira; Takahashi, Ryohei; Baluda, Redempta P.; Oliveros, Noel C.; Maglambayan, Victor B.; Luis, Roy Ronald C.; Faustino, Maria Lourdes M.; Almadin, Jacky
Abstract: The Southwest prospect is located at the southwestern periphery of the Sto. Tomas II porphyry copper–gold deposit in the Baguio District, northwestern Luzon, Philippines. The Southwest prospect hosts a copper‐gold mineralization related to a complex of porphyry intrusions, breccia facies, and overlapping porphyry‐type veinlets emplaced within the basement Pugo metavolcanics rocks and conglomerates of the Zigzag Formation. The occurrences of porphyry‐type veinlets and potassic alteration hosted in the complex are thought to be indications of the presence of blind porphyry deposits within the Sto. Tomas II vicinity. The complex is composed of at least four broadly mineralogically similar dioritic intrusive rocks that vary in texture and alteration type and intensity. These intrusions were accompanied with at least five breccia facies that were formed by the explosive brecciation, induced by the magmatic–hydrothermal processes and phreatomagmatic activities during the emplacement of the various intrusions. Hydrothermal alteration assemblages consisting of potassic, chlorite–magnetite, propylitic and sericite–chlorite alteration, and contemporaneous veinlet types were developed on the host rocks. Elevated copper and gold grades correspond to (a) chalcopyrite–bornite assemblage in the potassic alteration in the syn‐mineralization early‐mineralization diorite (EMD) and contemporaneous veinlets and (b) chalcopyrite‐rich mineralization associated with the chalcopyrite–magnetite–chlorite–actinolite±sericite veinlets contemporaneous with the chlorite–magnetite alteration. Erratic remarkable concentrations of gold were also present in the late‐mineralization Late Diorite (LD). High X Mg of calcic amphiboles (>0.60) in the intrusive rocks indicate that the magmas have been oxidizing since the early stages of crystallization, while a gap in the composition of Al between the rim and the cores of the calcic amphiboles in the EMD and LD indicate decompression at some point during the crystallization of these intrusive rocks. Fluid inclusion microthermometry suggests the trapping of immiscible fluids that formed the potassic alteration, associated ore mineralization, and sheeted quartz veinlets. The corresponding formation conditions of the shallower and deeper quartz veinlets were estimated at pressures of 50 and 30 MPa and temperatures of 554 and 436°C at depths of 1.9 and 1.1 km. Temperature data from the chlorite indicate that the chalcopyrite‐rich mineralization associated with the chlorite–magnetite alteration was formed at a much lower temperature (ca. 290°C) than the potassic alteration. Evidence from the vein offsetting matrix suggests multiple intrusions within the EMD, despite the K‐Ar ages of the potassic alteration in EMD and hornblende in the LD of about the same age at 3.5 ± 0.3 Ma. The K‐Ar age of the potassic alteration was likely to be thermally reset as a result of the overprinting hydrothermal alteration. The constrained K‐Ar ages also indicate earlier formed intrusive rocks in the Southwest prospect, possibly coeval to the earliest "dark diorite" intrusion in the Sto. Tomas II deposit. In addition, the range of δ 34 S of sulfide minerals from +1.8‰ to +5.1‰ in the Southwest prospect closely overlaps with the rest of the porphyry copper and epithermal deposits in the Sto. Tomas II deposit and its vicinity. This indicates that the sulfides may have formed from a homogeneous source of the porphyry copper deposits and epithermal deposits in the Sto. Tomas II orebody and its vicinity. The evidence presented in this work proves that the porphyry copper‐type veinlets and the adjacent potassic alteration in the Southwest prospect are formed earlier and at a shallower level in contrast with the other porphyry deposits in the Baguio District. Abstract : Evolution of the Southwest prospect. Base image modified from Philex Mining Corporation (unpublished). (a) Syn‐mineralization timeline indicating the early stage of porphyry copper mineralization in the Southwest prospect. The diagram shows the multiple phases of intrusion of the EMD magma and the effect of the potassic alteration to the wallrocks. The diagram also shows that PMBx‐1 destroyed the pre‐existing rocks and alteration envelope, along with the deposition of the contemporaneous sheeted quartz veinlets at their estimated depth of formation and distal chlorite–magnetite veinlets; (b) late‐mineralization timeline marked by the intrusion of the LD magma, resulting in the dilution of potassic alteration and mineralization and consequent overprinting chlorite–magnetite alteration and propylitic alteration in the adjacent rocks; (c) post‐porphyry copper mineralization timeline and late development of the hydrothermal system in the Southwest prospect. CGL, Conglomerate; DP, Diorite Porphyry; EMD, Early Mineralization Diorite; KTP, Keratophyre; LD, Late Diorite; MA, Meta‐andesite; ODP, Old Diorite Porphyry; PMBx‐1, Phreatomagmatic Breccia Facies 1; PMBx‐2a, Phreatomagmatic Breccia Facies 2a; PMBx‐2b, Phreatomagmatic Breccia Facies 2b